Case Report: High-Definition 4K-3D Exoscope for Removal of an Orbital Cavernous Hemangioma Using a Transpalpebral Approach - Peron, Stefano; Paulli, Stefano; Stefini, Roberto (Frontiers in Surgery, 2021)
Background: Cavernous hemangioma, also known as cavernous vascular malformation (CVM), is the most common primary lesion of the orbit in adults. The management of these lesions is challenging and is strongly dependent on their location, as well as the patient’s symptoms and expectations. The trans-palpebral approach is currently used in surgery for orbital tumors, anterior skull base tumors and, even more, orbital reconstruction, because of its well-demonstrated esthetic advantages. Similarly, the use of magnification can be provided by surgical loupes, microscope, or, more recently, endoscope, which is well documented for its advantages in terms of minimal invasiveness and safety. In the last years, the use of exoscopes in microsurgery has been proposed due to their greater and sharper intraoperative magnification, but never for the removal of orbital tumors. Clinical Presentation: We describe a case of a 38-year-old woman with a right orbital intraconic CVM removed using an inferior transpalpebral approach performed under 4K-3-dimensional (4K-3D) exoscopic vision. Navigation and ultrasound were also used, with the former allowing better identification of the lesion within the orbit and the second overcoming the limitations of navigation, in terms of the retraction on the ocular globe before or just after periorbital incision. Conclusion: The use of a 4K-3D exoscope allowed us to perform the surgery safely, thanks to the high magnification and definition of anatomical details, with the surgeon operating in an upright, comfortable position. The CVM was completely removed with excellent results from both functional and esthetic points of view.